Development of Operational and Teaching Software for a Complex Analytical Instrument Using Virtual Instrument Technology - Holmes, James R. (Curtin University, 2002)
It is not always possible to provide students and new users of complex instrumentation with sufficient hands-on use to fully develop the required knowledge of the instrument. Access may also be limited when there is a need to develop data collection and processing procedures. One solution to this problem is to develop a simulation of the instrument in readily accessible computer software. Modern computer-based technology allows traditional instrumentation to be replaced with Virtual Instruments consisting of digital control/acquisition hardware and software that graphically represents the functions of the physical instrument.In this thesis, operating and analysis software to simulate the operation of complex analytical instrumentation was successfully developed using a numerical model of the instrument. The approach will reduce the need for machine time for operator training and the development of data collection processing procedures. In particular the thesis developed software to emulate the behaviour of a VG-354 Thermal Ionisation Mass Spectrometer. Graphical programming tools were employed to create a modular set of Virtual Instruments that formed the basis of the model. The Simulated Mass Spectrometer produced results that compared well with real data obtained from the physical instrument.Virtual Instrument peak centring and measurement modules were then developed to operate the Simulated Mass Spectrometer in peak jumping mode. Uncertainties were reduced with improved analysis techniques employing polynomial least-squares fits for peak centring and single-collector isotope ratio measurements. The techniques also have the potential to accommodate hysteresis effects in the magnetic sector analyser, further reducing uncertainty.